Understanding plastics testing - Hylton, Donald C. (Hanser Publishers ; Hanser Gardner Publications, 2004)
This overview of plastics testing provides an understanding of how polymer structure and morphology affect properties that are important for plastics processing and how to test for these properties. The reader will get an overview of basic material testing, the specific properties tested, and why they are important.